K.C. Mehta and Manoranjan Mitra Award – Review Article - Use of molecular tools for understanding bacterial blight pathogen populations of rice and usefulness of disease resistance genes - SRIDHAR, R. (Indian Phytopathology, 2002)
Bacterial blight is one of the most serious diseases of rice (Ou, 1985) and also it is one of the oldest recorded rice diseases. It is known in Japan since 1884 and was called "white withering disease" (Tagami and Mizukami, 1962). Its bacterial nature was established and the bacterium was described in 1922 (Ishiyama, 1922). Subsequently it was reported from China (Siang, 1952), Thailand (Anonymous, 1958), the Philippines (Goto, 1964), Indonesia (Reitsuma and Schure, 1950), Sri Lanka (Pieris, 1962), Korea (Takeuchi, 1938), Taiwan (Hashioka, 1951), Malaysia (Singh, 1969), Kampuchea (Ou, 1985), Bangladesh (Alim, 1967), Australia (Buddenhagen et al., 1969), Latin America (Ou, 1977), USSR (Vzoroff, 1938) and United States (Jones et al., 1989). In the beginning, the causal organism of bacterial blight was called Bacillus oryzae Hori and Bokura (Dowson, 1939). According to Migula’s system, Ishiyama (1922) renamed the bacterium as Pseudomonas oryzae (Uyeda & lshiyarna). It was later transferred to Bacterium oryzae (Uyeda & Ishiyama) Nakata, and subsequently to Xanthomonas oryzae (Uyeda & Ishiyama) Dowson (Ou, 1985). According to the revision of the International Code of Nomenclature of Bacteria, the committee on Taxonomy of Phytopathogenic Bacteria of the International Society for Plant Pathology has adopted the name Xanthomonas campestris pv. oryzae (Ishiyama, 1922) Dye (Dye, 1978, Dye et al., 1980). Now it has been renamed as Xanthomonas oryzae pv. oryzae (ex Ishiyama, 1922). sp. nov, nom. rev. (formerly designated X. campestris pv. oryzae) (Swings et et., 1990).